Processing Of Heavy Minerals From Terengganu Silica Sand - Muhamad Zaki, Nur Amierah An-Nissa' (Universiti Sains Malaysia, 2018)
The purpose of this research is to characterize sample silica and to recover the valuable minerals found in silica samples obtained from in Terengganu Silica Sand. There are six methods of characterization were implemented in this research such as Particle Size Distribution, Loss on Ignition, X-ray Fluorescence (XRF), Microscopic Study, Panning and Magnetic Separation. From this study, corundum (Al₂Oɜ), silica (SiO₂), rutile (TiO₂), and hematite (Fe₂Oɜ) were found in amang Terengganu Silica Sand. The size of the sample that was chosen for this the research is the ranges from +600 µm to -212 µm. As the result, from composition analysis, the composition of corundum was increase when the size of particle is decrease. However, this sample is from the gangue mineral of silica, but there is still have a higher amount of silica that are still present in the waste.